Every last one [compact disc, unabridged] : a novel - Quindlen, Anna (Simon & Schuster Audio, 2010)
Mary Beth Latham is first and foremost a mother, whose three teenaged children come first, before her career as a landscape gardener, or even her life as the wife of a doctor. Caring for her family and preserving their everyday life is paramount. When one of her sons, Max, becomes depressed, Mary Beth becomes focused on him, and is blindsided by a shocking act of violence.